How to Read "Silence" in a Literary Text without a Teacher: ODL Learners' Perceptions of Studying Literary Texts through the Online Mode - Lal Medawattegedara; Vivimarie Vanderpoorten Medawattegedera (The Open University of Sri Lanka, 2022)
Teaching literature is a complex and challenging task, particularly because of the multiple interpretive possibilities of literary texts. It is even more so when teaching English poetry to learners for whom English is a second language. Further, Literature has been traditionally been a subject that needs the presence of a teacher to assist students in their quest to read for deeper understanding and interpretation of texts. This study investigated second-year undergraduates' perceptions on learning T.S. Eliot's epic poem The Waste Land - a notedly difficult text to access, owing to its length as well as the need for compulsory background reading on history, mythology, Eastern and Western philosophy and the Classics - via both an online intervention and an in-person Day School, using a qualitative research design and in-depth semi-structured interviews. The study found that the BA in English and English Language Teaching students view the online component of the course as useful but supplementary in its function, that online learning cannot replace the teacher in a physical classroom and that they prefer the physical presence of a teacher when attempting to read, understand and interpret the literary text. However, they value the online component especially when it facilitates feedback on writing about Literature, and when it offers language-related feedback with regard to assessments.